CHALLENGING THE NURNEY PROCEDURE BY THE ROMA NATIONAL COMMUNITY (Heritage, 2020)
World War II is considered to be the largest and longest bloody conflict in recent history. It began with the German attack on Poland on September 1, 1939. The war lasted six years and ended with the capitulation of Japan on September 2, 1945. The consequences of the war are still present in many countries today. "German, Italian and Japanese fascists waged a war of conquest with the aim of dividing the world and creating a new order in which it would have economic, political and military domination, establish a rule of terror and violence and destroy all forms of human freedom, dignity and humanism.Only a few thousand Roma in Germany survived the Holocaust and Nazi concentration camps. Trying to rebuild their lives, after losing so many family members and relatives, and after their property was destroyed or confiscated, they faced enormous difficulties. The health of many was destroyed. Although they have been trying to get compensation for that for years, such requests have been constantly deniedBased on established facts, eyewitnesses, witnesses, historical and legal documents, during the Second World War, the crime of genocide against Orthodox Serbs, Jews and Roma of all faiths except Islam was committed. The attempt to exterminate the Roma during the Second World War must not be forgotten.There was no justice for the survivors of the post-Hitler era. It is important to note that the trial in Nuremberg did not mention the genocide of the Roma at all.The Nuremberg trial is basically the punishment of the losers by the winners. This is visible even today because these forces rule the world. Innocent victims, primarily Roma, have not received justice, satisfaction or recognition from the world community.The Roma were further humiliated because they were not given a chance to speak about the few surviving witnesses about the victims and the horrors they survived. The Roma for the Nuremberg International Military Court and the Nuremberg judges simply did not exist, which called into question the legal aspect of the process, which has not been corrected to date. The Roma national community is committed to revising history, to reviewing the work of the Nuremberg tribunal.
Keywords: World War II, establishment of an international military tribunal, Nuremberg Trials, trial of war criminals, Crime against peace, Crime against humanity, crime of genocide, reasons for challenging the Nuremberg Trials.